Stocks Performance around earnings announcements: empirical evidence from the FTSE 100 - Bourreau, Charly (2017)
This paper investigates the stock price behaviour of FTSE 100 companies around their earnings announcements. The investigation relies on the analysis of the stock price behaviour around 1009 publications. Each time, the influence of the event was analysed during a 75 days’ period. This window includes the seven weeks before and after the announcements as well as the weeks of publication. Both the index adjusted and mean adjusted approaches were followed for each of our event studies. For the purpose of the second approach, the estimation period used was stretched from 1st January 2010 to the 31st December 2015. The average daily compounded returns and standard deviation measures and a simulation of GARCH parameters were calculated for each earnings publication.